Improved interface properties of atomic-layer-deposited HfO2 film on InP using interface sulfur passivation with H2S pre-deposition annealing - Jin, Hyun Soo; Cho, Young Jin; Seok, Tae Jun; Kim, Dae Hyun; Kim, Dae Woong; Lee, Sang-Moon; Park, Jong-Bong; Yun, Dong-Jin; Kim, Seong Keun; Hwang, Cheol Seong; Park, Tae Joo (ELSEVIER, 2015)
Surface sulfur (S) passivation on InP substrate was performed using a dry process - rapid thermal annealing under H2S atmosphere for III-V compound-semiconductor-based devices. The electrical properties of metal-oxide-semiconductor capacitor fabricated with atomic-layer-deposited HfO2 film as a gate insulator were examined, and were compared with the similar devices with S passivation using a wet process - (NH4)(2)S solution treatment. The H2S annealing provided solid S passivation with the strong resistance against oxidation compared with the (NH4)(2)S solution treatment, although S profiles at the interface of HfO2/InP were similar. The decrease in electrical thickness of the gate insulator by S passivation was similar for both methods. However, the H2S annealing was more effective to suppress interface state density near the valence band edge, because thermal energy during the annealing resulted in stronger S bonding and InP surface reconstruction. Moreover, the flatband voltage shift by constant voltage stress was lower for the device with H2S annealing. (C) 2015 Elsevier B.V. All rights reserved.